Thomas Aquinas on war and peace - Reichberg, Gregory M. (Cambridge University Press, 2017)
Just war in Aquinas's typology of the virtues -- Just war among the quaestiones on charity -- War's permissibility -- Interpreting the gospel precepts of patience -- Military prudence -- Battlefield courage -- Selected topics -- Legitimate authority -- War and punishment -- Self-defense -- Preventive war -- The moral equality of combatants -- St. Thomas and the doctrine of Bellum Iustum today